"Ut pictura poiesis": text i imatge, mimesi i realitat quant a «Tirant lo Blanch» - Martines, Vicent (Caplletra. Revista Internacional de Filologia, 2007)
The relationship between literature and reality in the Middle Ages can be considered from several dimensions. One of the most important cultural elements of the medieval period is the visual representation of reality found it literary texts, not only through the presence of miniatures in the manuscripts, but especially through the description of realia in the same text. The encyclopedic tradition helps to intertwine this close relationship between the outer representativeness and the inwardness of the text, a new interpretation of the Horacian’s ut pictura poiesis. The «Tirant lo Blanch» is a fictional text full of iconic references to contemporary reality, which in this study are made clear visually.